2023
DOI: 10.1227/neu.0000000000002381
|View full text |Cite
|
Sign up to set email alerts
|

Systematic Review and Meta-Analysis of Randomized Controlled Trials for Scalp Block in Craniotomy

Abstract: BACKGROUND: Scalp block is regional anesthetic injection along nerves innervating the cranium. Scalp blocks for craniotomy may decrease postoperative pain and opioid consumption. Benefits may extend beyond the anesthetic period. OBJECTIVE:To analyze evidence for scalp block on postoperative pain and opioid use. METHODS: This systematic review and meta-analysis, Prospective Register of Systematic Reviews registration (CRD42022308048), included Ovid Medical Literature Analysis and Retrieval System Online, Embase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 47 publications
(81 reference statements)
0
4
0
Order By: Relevance
“…Additional benefits of scalp blocks and wound/pin site infiltration showed by Akcil et al, 8 in a randomized trial of patients undergoing infratentorial craniotomy, included reduced cumulative morphine consumption and early postoperative pain scores compared with no intervention. Indeed, meta-analyses have consistently corroborated findings of superior early postoperative pain control in patients receiving scalp blocks 5,9,10 . Published studies suggest scalp blocks may be superior to scalp infiltration 11–13 …”
Section: Scalp Blocksmentioning
confidence: 92%
See 3 more Smart Citations
“…Additional benefits of scalp blocks and wound/pin site infiltration showed by Akcil et al, 8 in a randomized trial of patients undergoing infratentorial craniotomy, included reduced cumulative morphine consumption and early postoperative pain scores compared with no intervention. Indeed, meta-analyses have consistently corroborated findings of superior early postoperative pain control in patients receiving scalp blocks 5,9,10 . Published studies suggest scalp blocks may be superior to scalp infiltration 11–13 …”
Section: Scalp Blocksmentioning
confidence: 92%
“…However, the overall incidence of complications directly related to scalp blocks is vanishingly low. In a recent meta-analysis of 22 randomized control trials in 1550 patients on scalp blocks in craniotomy, none of the included studies reported any adverse events attributable to scalp blocks, even though blocks were performed using anatomic landmarks and various LA concentrations, additives, and volumes 9 …”
Section: Scalp Blocksmentioning
confidence: 99%
See 2 more Smart Citations